2020
DOI: 10.3390/v12010079
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Porcine Deltacoronavirus and Alteration of Immunoglobulin Transport Receptors in the Intestinal Mucosa of PDCoV-Infected Piglets

Abstract: Porcine deltacoronavirus (PDCoV) is a porcine enteropathogenic coronavirus that causes watery diarrhea, vomiting, and frequently death in piglets, causing serious economic losses to the pig industry. The strain CHN-JS-2017 was isolated and identified by cytopathology, immunofluorescence assays, transmission electron microscopy, and sequence analysis. A nucleotide sequence alignment showed that the whole genome of CHN-JS-2017 is 97.4%-99.6% identical to other PDCoV strains. The pathogenicity of the CHN-JS-2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It was previously shown that infection with the porcine transmissible gastroenteritis virus (TGEV) belonging to the coronavirus family can cause an increase of FcRn expression in the normal porcine intestinal cell line IPEC-J2 by activating NF-κB signaling through membrane receptors of the Toll-like receptor family and increasing pro-inflammatory cytokine levels ( 157 , 158 ). Conversely, infection with the CHN-JS-2017 strain of porcine deltacoronavirus PDCoV in piglets was associated with NF-κB pathway suppression and decreased FcRn and pIgR expression in the intestinal epithelium, which may enable the virus to avoid secreted neutralizing antibodies ( 159 ). Thus, SARS-CoV and SARS-CoV-2 infection can both theoretically increase FcRn and pIgR expression and antibody-mediated virus transcytosis across the intestinal barrier.…”
Section: Using Tissue Barrier Models To Study Coronavirus Transcytosismentioning
confidence: 99%
“…It was previously shown that infection with the porcine transmissible gastroenteritis virus (TGEV) belonging to the coronavirus family can cause an increase of FcRn expression in the normal porcine intestinal cell line IPEC-J2 by activating NF-κB signaling through membrane receptors of the Toll-like receptor family and increasing pro-inflammatory cytokine levels ( 157 , 158 ). Conversely, infection with the CHN-JS-2017 strain of porcine deltacoronavirus PDCoV in piglets was associated with NF-κB pathway suppression and decreased FcRn and pIgR expression in the intestinal epithelium, which may enable the virus to avoid secreted neutralizing antibodies ( 159 ). Thus, SARS-CoV and SARS-CoV-2 infection can both theoretically increase FcRn and pIgR expression and antibody-mediated virus transcytosis across the intestinal barrier.…”
Section: Using Tissue Barrier Models To Study Coronavirus Transcytosismentioning
confidence: 99%
“…Virus isolation and identification is the most commonly used pathogen detection method, but is complicated and time-consuming [ 30 ]. PCR and real-time PCR instruments are expensive and difficult to use.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations of TGEV, PEDV, PDCoV and SADS-CoV infections are very similar and mainly include loss of appetite, diarrhea and vomiting, that lead to dehydration, weight loss, lethargy and death (Wang et al 2019;Qian et al 2020). Clinical symptoms appear 1-3 days after infection and usually do not last longer than 10 days.…”
Section: Pathogenesis Of Enteric Coronavirus Infections In Pigsmentioning
confidence: 99%